Different functional groups functionalized hexagonal boron nitride (h-BN) nanoparticles and multi-walled carbon nanotubes (MWCNT) for hydrogen storage. (1st November 2021) - Doğan, Mehmet; Selek, Ayşe; Turhan, Onur; Kızılduman, Berna Koçer; Bicil, Zeynep
Highlights: The modified h-BNs and MWCNTs were produced and studied their H2 adsorption performances. Hydrogen storage capacity of h-BN increased with the modification. Hydrogen storage capacity of MWCNT dependent on surface area and functional group. Samples had higher hydrogen storage capacity at high pressure and low temperature. Adsorption-desorption isotherms at 77 K are compatible with Type IV. The MWCNT-COCl had the highest hydrogen storage capacity. Abstract: The hexagonal boron nitride (h-BN) functionalized with p-phenylenediamine, multi-walled carbon nanotubes (MWCNT) functionalized with carboxyl and acylchloride groups, and h-BN-Ph-NH-CO-MWCNT structure were produced by coupling, oxidation, acylation and amide formation reactions under various conditions and then, characterized by Brunauer-Emmett-Teller (BET), Fourier transform infrared spectroscopy-Attenuated total reflectance (FTIR-ATR), thermogravimetric and differential thermal analysis (DTA/TG), X-ray diffraction (XRD), and scanning electron microscopy (SEM) instruments. The hydrogen storage capacities of the samples were measured as a function of pressure at different temperatures. The h-BN and MWCNT surfaces were successfully modified. BET surface area of h-BN increased with the modification while those of other MWCNTs except for MWCNT-COCl (COCl: acylchloride group) decreased. While the hydrogen storage capacity of h-BN increased with the modification parallel to the BET surface areas of the samples, the hydrogen storage capacity of MWCNT varied depending on the BET surface area and functional group. The MWCNT-COCl had the highest hydrogen storage capacity. The samples had higher hydrogen storage capacity at the cryogenic temperature. Hydrogen adsorption isotherms conformed to Henry's law at room temperature and showed multi-layer adsorption behavior at cryogenic temperature. Hydrogen storage capacity of the samples increased with increasing pressure. Adsorption-desorption isotherm curves at cryogenic temperature were quite compatible with Type IV isotherm. The results show that the functionalization and especially the acyl group play an important role in increasing the hydrogen storage capacity of h-BN and MWCNT.